PENGARUH KEPEMIMPINAN DAN PENEMPATAN KERJA TERHADAP KINERJA KARYAWAN PT. BIAS NUSATAMA DENGAN KEPUASAN KERJA SEBAGAI VARIABEL MODERASI DI WAREHOUSE DURI 125 - Guela Restu; Machasin -; Kurniawaty Fitri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
This study aims to analyze the influence of leadership and job placement PT. Bias Nusatama on employee performance and job satisfaction as a moderating variable in Warehouse Duri 125. This study used 70 samples. The analytical method used is descriptive analysis method is a way to test variables, regression test, and the last test path analysis or path analysis.From the results of testing that has been done, no direct relationship to the leadership variable variable variable performance through job satisfaction on employee PT. Bias Nusatama is greater than the result of a direct relationship leadership variable to variable performance. Indirect relationship to the employment variable variable variable performance through job satisfaction on employee PT. Bias Nusatama is smaller than the result of a direct relationship to the employment variable performance variables.Variable leadership, job placement, employee performance and job satisfaction of employees of PT. Nusatama bias is low can be enhanced with innovations and new techniques in working in the field that can accelerate the process of completion of work by employees, other than the party leader should give the employees an equal opportunity to advance by the company, and in the placement of employees is in accordance with the educational background and work experience which is owned by the employee and provide appropriate salaries to employees. So that the performance of the employee of PT. Bias Nusatama in Warehouse Duri 125 can be increased.Keywords: Leadership, Employment, Employee Performance, Job Satisfaction.